2015
DOI: 10.1021/es5053039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Manure-Application Practices on Curli Production by Escherichia coli Transported through Soil

Abstract: The release of Escherichia coli into the environment from untreated manure can pose a threat to human health. Environmental survival of E. coli has been linked to extracellular fibers called curli. We investigated the effect of manure management (surface application followed by incorporation versus immediate incorporation) on the relative abundance of curli-producing E. coli in subsurface drainage effluent. Samples were collected from three dairy farms. The proportion of curli-producing E. coli in the manure s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Bioinformatic analyses of some of the main genes required for curli production (such as csgD , csgB , csgA and csgD promoters) revealed wild type alleles in the strains lacking curli production. The presence of wild type curli subunit genes in E. coli strains do not always result in curli production and this has been reported by several authors in E. coli ( Dyer et al, 2007 ; Truhlar et al, 2015 ), Salmonella spp. ( De Oliveira et al, 2014 ) and Enterobacter sakazakii ( Zogaj et al, 2003 ).…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Bioinformatic analyses of some of the main genes required for curli production (such as csgD , csgB , csgA and csgD promoters) revealed wild type alleles in the strains lacking curli production. The presence of wild type curli subunit genes in E. coli strains do not always result in curli production and this has been reported by several authors in E. coli ( Dyer et al, 2007 ; Truhlar et al, 2015 ), Salmonella spp. ( De Oliveira et al, 2014 ) and Enterobacter sakazakii ( Zogaj et al, 2003 ).…”
Section: Discussionmentioning
confidence: 70%
“…The heterogeneity in curli production may reflect the genetic diversity of E. coli lineages present in the soil, perhaps suggesting that they have evolved to occupy different localized niches in the soil, with some of the niches not requiring the ability to retain curli. Evidence supporting this hypothesis comes from a study by Truhlar et al (2015) , which showed that the population of E. coli curli producers was maintained at a higher level when manure was spread on the surface of the soil than when it was injected into the soil. The selection for retention of curli on the soil surface was proposed to be based on a need for protective biofilm to help overcome UV radiation and desiccation, which would not be encountered below the soil surface ( Truhlar et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Untreated manure can carry harmful bacteria (e.g., pathogens) to soil, which can survive for weeks and transfer to the edible crop parts with time [16]. Land-application of animal manure also enables bacterial pathogens to reach groundwater and adversely affect ecosystem and human health [17][18][19][20]. ough it is normally a benign commensal organism and used as a proxy for enteric pathogens, several E. coli strains are pathogenic and can cause severe hemorrhagic colitis and hemolytic uremia in humans [15,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%